The Arrival of Islam in Indonesia: A Theory of Islam's Spread - Shofura, Syifa; Ihsan, Muhammad; Al-Latifatuzzahra, Siti Safira (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
The arrival of Islam in the archipelago is currently still being debated, due to the lack of reliable scientific data and evidence, as well as the one-sided attitude of various theories. It is very possible that these theories prioritize one aspect while ignoring others. As a result, most of the existing theories cannot explain how Muslimization occurred and how Islam entered the archipelago.This research uses Library Research which focuses on history. The aim of this paper is to investigate the theories that support the spread of Islam in the archipelago. The four theories discussed today show how Islam entered the archipelago. There are several advantages and disadvantages to each of these theories, and one thing that is certain from all of these theories is that Islam developed in the archipelago peacefully, unlike Christianity which had a goal.